МЕМУАРЛЫҚ ШЫҒАРМАЛАРДА МИЛЛЕТ ЗЫЯЛЫЛАРЫ ТӘҒДИРИ (Қ.Камаловтың мемуарлық шығармалары мысалында) - Нурабуллаев, Б.Х. (SCIENCE and SOCIETY, 2021)
In the article, the author scientifically analyzes the interpretation of the fate of the nation’s intelligentsia in his memoirs. The memoir explores the portrayal of politics of the time and the importance of this work as a historical basis for contemporary political activists.